Allergic patients with and without allergen-specific immunotherapy mount protective immune responses to tick-borne encephalitis vaccination in absence of enhanced side effects or propagation of their Th2 bias. Issue 20 (11th May 2018) - Garner-Spitzer, Erika; Seidl-Friedrich, Claudia; Zwazl, Ines; Hofer, Michael; Kinaciyan, Tamar; Jarisch, Reinhart; Stiasny, Karin; Zlabinger, Gerhard J.; Kundi, Michael; Wiedermann, Ursula
Highlights: TBE antibody titers are comparable between allergic and healthy subjects. Specific immunotherapy does not limit protective TBE vaccine responses. Vaccinating allergic patients does not propagate Th2 immune responses or allergic symptoms. Allergic and healthy subjects have similar reactogenicity profiles. No indication to postpone vaccinations in allergic patients, even under SIT. Abstract: Background: Allergic diseases are caused by Th2-driven immune responses and their treatment with specific immunotherapy (SIT) leads to immunomodulation via IL10, TGF-ß and Th1/Tr1 shift. This phase IV, open-label clinical trial investigated whether allergies and SIT treatment influenced immune responses to routine vaccination. Methods: We studied three groups: 49 allergic patients (allergic group), 21 allergic patients receiving maintenance doses of SIT (SIT group), and 49 non-allergic controls. All subjects received tick-borne encephalitis (TBE) booster vaccines and humoral and cellular immune responses were evaluated after one week, four weeks and six months. Results: The levels and kinetics of neutralizing TBE-specific antibodies, reflecting protection against TBE, were not significantly different in the three groups. The allergic group showed Th2 polarization pre-booster as indicated by increased TBE-specific IgG1 and elevated mitogen-induced IL5 production. Alum-adjuvanted TBE vaccine led to Th2 biased immune responses in the controls, but to no further enhancement of Th2 polarization in the allergic and SIT group. Furthermore, in the SIT group cellular parameters reflected the induction of immunomodulation due to increased Tregs, elevated baseline IL10 and lack of TBE-specific IL5. Importantly, these cellular regulatory responses did not limit the ability to mount sufficient TBE-specific antibodies after the booster. All groups tolerated the vaccine well with no exacerbation of allergic symptoms. Conclusion: TBE booster vaccinations were immunogenic and safe in both the allergic and SIT group and contributed to balanced immune responses. Our data indicate that all allergic patients, even when undergoing SIT, should be vaccinated without hesitation and at regular intervals according to standard recommendations. ClinicalTrials.gov (NCT02511535 ).